Use of the wii balance board to assess changes in postural balance across athletic season. Issue 11 (25th May 2017) - Cullen, Hilary M; Sun, Yao; Christie, Brian R; Paul Zehr, E
Abstract : Objective: The purpose of this study was to investigate potential utility of a customised Wii Balance Board (WBB) program to assess postural balance in an athletic population. Researchers hypothesised that WBB measures would be strongly correlated to the Balance Error Scoring System (BESS) used in concussion assessments. Design: Cross-sectional time series. Static and dynamic balance was assessed using the WBB and BESS at three time points of an athletic season: 1) pre-season, 2) mid-season, and 3) post-season. Setting: University research laboratory Subjects Intervention Outcome measures: 1) BESS, 2) WBB dynamic recovery time, and 3) WBB static Centre of Pressure (COP). Results: WBB COP data were found to be strongly correlated with BESS scores across all time points [pre-season (r=0.689, p<0.05), mid-season (r=0.767, p<0.01), and post-season (r=0.780, p<0.01)]. There were significant differences in recovery time (p<0.005) and COPx variance for the single-leg BESS condition across all time points (p<0.005). No significant differences were observed in raw BESS scores across time points. Conclusions: Study results support the use of a WBB as an objective tool in measuring variance in static and dynamic postural balance. This program has potential utility for clinicians when assessing balance deficits related to concussion. Planned work will examine the use of the WBB program in measuring variance in postural balance in individuals with sport-related concussion. Competing interests: None.